The mediating role of positivity in the relationship between psychological immunity and emotional control among health sector workers in Erbil city - Aziz, Izaddin Ahmad; Mahmood, Delan Abdullah (Journal of Educational and Psychological Sciences, 2023)
This research aims to examine the mediating role of positivity in determining the relationship between psychological immunity and emotional control among health sector workers. In addition, identify the significance of differences in psychological immunity among members of the research sample according to the variables of gender and years of service. The study sample consisted of 310 of both sexes. To measure the variables of the study, the researchers used ready-made scales. To measure psychological immunity, the Choochom (2013) scale was used, consisting of 14 items. It measures three domains, which are resilience, self-freedom, hope, compatibility, and awareness. As for the positive self-measure, the two researchers relied on the (2017) Abdul Khaleq scale, which consisted of 16 items. To measure emotional control, the Gross & John (2003) scale was used, consisting of 10 items. Two researchers extracted the psychometric characteristics of the three scales of validity and reliability. After analyzing the data, the results of the study indicated that the research sample members enjoy a high degree of psychological immunity, positive self-esteem, and emotional control. The number of statistically significant differences in the gender variable and years of service for the three variables. The results indicated that there is a significant correlation at the level of significance between psychological immunity, positive self, and emotional control. Using regression analysis to measure the predictive ability of psychological immunity and positive self, the results indicated that the subjective freedom domain of psychological immunity and positive self are good predictors of emotional control. Considering the results of the study, the researchers made several recommendations and proposals.
Keywords: psychological immunity; positive self; emotional control; workers in the health sector